2004
DOI: 10.1158/0008-5472.can-04-0648
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrogen Peroxide-Mediated Cytosolic Acidification Is a Signal for Mitochondrial Translocation of Bax during Drug-Induced Apoptosis of Tumor Cells

Abstract: Absence of the proapoptotic protein Bax renders tumor cells resistant to drug-induced apoptosis. We have shown that hydrogen peroxide (H 2 O 2 )-mediated cytosolic acidification is an effector mechanism during drug-induced apoptosis of tumor cells. Here, we report that Bax is critical in determining the sensitivity of tumor cells to H 2 O 2 -induced apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 50 publications
7
99
2
Order By: Relevance
“…However, other data seem to suggest that activation of the PI3K-Akt pathway could generate other reactive species like nitric oxide and superoxide, which would further enhance the downstream effects of this pathway (33)(34)(35)(36). These are intriguing findings, given our previous reports highlighting the role of intracellular redox status in the sensitivity of cancer cells to death stimuli (37)(38)(39)(40)(41)(42)(43)(44). We showed that a slight pro-oxidant intracellular milieu, invariably associated with the transformed phenotype, favors cell survival either by its positive effect on cell proliferation (45) or by impeding death execution pathway(s) (41,43,44,46).…”
Section: Introductionmentioning
confidence: 77%
“…However, other data seem to suggest that activation of the PI3K-Akt pathway could generate other reactive species like nitric oxide and superoxide, which would further enhance the downstream effects of this pathway (33)(34)(35)(36). These are intriguing findings, given our previous reports highlighting the role of intracellular redox status in the sensitivity of cancer cells to death stimuli (37)(38)(39)(40)(41)(42)(43)(44). We showed that a slight pro-oxidant intracellular milieu, invariably associated with the transformed phenotype, favors cell survival either by its positive effect on cell proliferation (45) or by impeding death execution pathway(s) (41,43,44,46).…”
Section: Introductionmentioning
confidence: 77%
“…One common cellular response to a number of oxidative and metabolic challenges is a reduction of intracellular pH (pHi) [36,39,40]; this is likely an early and essential event during apoptosis and/or necrosis [41]. Mechanisms proposed for cytosolic acidification include: dysregulation of ion transport [42]; proton leakage from acidic organelles [43]; and hydrolysis of high energy nucleotides [44].…”
Section: Oxidative and Metabolic Stresses Induce Cytosolic Acidificationmentioning
confidence: 99%
“…27,28 This view is, however, questioned by studies demonstrating that resveratrol-mediated apoptosis is, at least in part, independent on Bax but mostly related to the Bax/Bak inactivation. 29 p53 modulation.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%